Aplikasi Sistem Pendukung Keputusan Menggunakan Algoritma C5 Untuk Menentukan Penerima Bantuan Sosial - Solifiah Batubara, Febi; Halim Hasugian, Abdul; Santoso, Heri (Jurnal Ilmiah Binary STMIK Bina Nusantara Jaya, 2023)
Poverty is one of the development problems in various fields which is characterized by high unemployment, underdevelopment and deterioration caused by change. Most of the residents of Setia village, Pahae Jae sub-district, still have many poor people, the poverty rate is still high and they have implemented a social assistance system for the poor or underprivileged to reduce poverty. However, it turns out that the selection of social assistance recipients in the Setia Village area, Pahae Jae District is still using a manual system. the selection process is carried out by observing the residents' files from the start of the process to who can receive assistance based on the criteria that have been determined in the social section. So that the settlement process in determining the prospective recipients of social assistance does not occur systematically and sometimes is not on target, the decision tree algorithm c5.0 method was chosen by the author to speed up and facilitate the selection of eligible citizens to receive social assistance. the criteria are processed so that and obtain a value that will be compared with the training data, this research is an application of the classification of eligible and unworthy social assistance recipients. building this program or application can help make it easier for the village to determine recipients of the social assistance program for underprivile ged families.